Social action, raw material of Sociology (Research, Society and Development, 2021)
Individuals inhabit societies and it is in this environment that social action occurs, when the individual establishes a meaningful relationship, that is, when he/she tries to establish some type of communication while performing a social action with other individual(s). Social action takes place between individual(s) when it concerns the behavior of others and is guided by them for its development. (Weber, 1921). Sociology goes beyond the simple study of the conditions of social existence of human beings. (Fernandes, 1960). Qualitative, explanatory research, based on a literature review insofar as it seeks to explain the social action produced in society as the raw material for the study of Sociology.  The science seeks to understand social interactions, developed during social actions, in the most diverse types of human groupings. The maintenance of society needs to be preserved with a collective moral, in the social division of labor, organic solidarity managed by traditions, habits, values and moral codes that guide the life of individuals in society. It is concluded that socialization guides and organizes the development of man in accordance with the goals society pursues.